MARXIST CATEGORIES AND ANALYSIS OF THE SPACE CAPITALIST VALORIZATION PROCESS - Godoy, Paulo [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2018)
The article presents considerations about the process of capitalist valorization of space from two categories that are, in the perspective of the analysis undertaken here, fundamentals to the explanation of the relationship among value and space: land rent and fixed capital. The objective is to expose the capitalist property of the land, the social division of labor and the concentration and centralization of capital as being the general social determinations which historically produce the forms of capitalist valorization of space. The specific mode of circulation of fixed capital as a qualifier of space, through the functions of incorporating value to the soil and its abstract expression in the form of interests, is analyzed in the field of capitalist practices of differential appropriation of space-commodity in the turnover of the monetary capital. The article is organized in two sections: the first one deals with the concrete realizations conditions of successive separations between direct producer and means of production: the capitalist property of the land. Agricultural income, as a fraction of goodwill, and its link with the credit system, through the interests rates, constitute the initial elements for the analysis of the transformation of the space into commodity. The second section consists of specific analysis in the peculiar ways of circulation of fixed capital as a qualification of the process of capitalist valorization of space through the connection amongst agrarian income, interest rates and credit system, and monetary capital.
Keywords: Valorization of space; Land rent; Fixed capital